Case Report: Early 68Ga-PSMA-PET Metabolic Assessment and Response to Systemic Treatment for First-Line Metastatic Clear Cell Renal Cell Carcinoma; About Two Clinical Cases - Seront, Emmanuel; Lhommel, Renaud; Tombal, Bertrand (Frontiers in Oncology, 2021)
Early evaluation of response to anticancer treatment in metastatic renal cell carcinoma (RCC) is challenging as responses are sometimes delayed, as mixed responses can occur and as conventional imaging have some limitations. As PSMA has been previously identified in neovasculature of clear cell RCC (ccRCC), 68Ga-PSMA-Positron Emitted Tomography (PET) could appear as an interesting tool to evaluate therapeutic response. We describe the association of an early decrease in 68Ga metabolism (at 8 weeks after treatment onset) and further radiological response (at 12 weeks after treatment onset) to treatment in two patients with different sensitivity to axitinib - pembrolizumab combination. Interestingly, one of these patients presented an initial progressive disease on pembrolizumab alone and a subsequent response to axitinib alone in the disease course; these response profiles were associated with absence of decrease and subsequent decrease in the 68Ga metabolism, respectively. Even if further prospective trials are needed, 68Ga-PSMA-PET may appear as a promising way for early prediction of response to ccRCC systemic treatment.